دراسة مقارنة في الحرج الموقفي ودافع الإنجاز الدراسي في الجمناستك الفني بين طالبات كلية التربية البدنية وعلوم الرياضة - المفتي، بريفان عبدالله; سعيد، سعيد نزار; صالح، هيوا جلال (جامعة بابل - كلية التربية الرياضية, 2019)
اعتاد معظم مدرسي ومدرسات الجمناستك باستخدام أساليب التدريس الاعتيادية غير أبهين بالفروقات الفردية وخاصة للطالبات ولم يتم الاهتمام كثيرا بالخلفية البيئية للطالبات حول أجهزة الجمناستك وأن معظم الطالبات لم يعرفن شيئاً عن تلك الأجهزة وأثناء الممارسة العملية لدروس الجمناستك الفني يتفاجأن الطالبات بتنوع وتعدد الأجهزة وصعوبة المهارات عليهن، مما يتعرضن إلى حالات نفسية ومواقف محرجة عندما يجبرن على الأداء من قبل المدرسات كونه واجب لتحديد مستوى النجاح في المرحلة الدراسية أن هذه المواقف تسمى (بالحرج الموقفي) كما إن المشكلات التي تواجه طلبة كلية التربية البدنية وعلوم الرياضة أثناء عملية التعليم كثيرة منها مشكلات دراسية واقتصادية وجسمية واجتماعية نفسية وشخصية نفسية وعائلية والتي تؤثر بشكل سلبي على انجازهم الدراسي وخصوصاً في درس الجمناستك لصعوبة تعلم وأداء مهاراته، إذ إن إرشاد الطلبة يجب أن يعتمد على فهم قدراتهم واحتياجاتهم وطموحاتهم من أجل مساعدتهم في حل مشكلاتهم ومن هنا برزت مشكلة البحث في معرفة الفروق في الحرج الموقفي ودافعية الإنجاز الدراسي في الجمناستك الفني بين طالبات كلية التربية البدنية وعلوم الرياضة وهدف البحث إلى: - التعرف على الفروق في الحرج الموقفي ودافعية الإنجاز الدراسي في الجمناستك الفني بين طالبات كلية التربية البدنية وعلوم الرياضة.
Most of the teachers of the gymnastics used to use the usual teaching methods, and they did not care about the individual differences, especially for the female students. There was little attention to the environmental background of the female students about the gymnastic device and most of female students know nothing about these devices. And through practicing lessons of gymnastics, the female students are surprised to see various of devices and the difficulty of performing skills on those devices. Therefore, it leads them to psychological and embarrassing situations when they are obliged to perform by teachers being a duty to determine the level of success in the school stage and these are called embarrassing attitudes. The problems that face students of the Faculty of Physical Education and Sport Sciences during the educational process are many, including study, economic, physical, social, psychological and personal and family problems, which negatively affect their academic achievement, especially in the study of gymnastics because of the difficulty of learning and the performance of his skills. Since guiding students rely on an understanding of their abilities, needs and aspirations in order to help them solve their problems, and hence the problem of research emerged to identify the differences embarrassing attitude and motivation of academic achievement in artistic gymnastics among female students of the Faculty of Physical Education and Sports Science. The research aims to identify the differences in embarrassing attitude and motivation of academic achievement in artistic gymnastics technicians students of the Faculty of Physical Education and Sports Science
Keywords: الأساليب التدرسية -- الانجاز الدراسي -- طلبة الجامعات -- الجمناستك الفني